Manajemen Konten Digital pada Instagram @fraksipkssumut - Anisa Shelomitha Br Berutu; Fakhrur Rozi (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the content management of the Instagram account @fraksipkssumut as a digital political communication medium for the Prosperous Justice Party (PKS) faction of the North Sumatra Provincial Legislative Council (DPRD). This study is crucial for understanding the role of social media as a strategic instrument in building political communication in the digital era. This research employed a qualitative approach, with data collection techniques including account activity observation, Instagram Insight analysis, and in-depth interviews. Data were analyzed to identify content management patterns and implemented communication strategies. The results indicate that content management is structured through faction agenda-based planning, centralized organization by account administrators, and adaptive content implementation for digital visual formats such as reels. Content performance is evaluated through digital metrics, particularly engagement levels, which indicate that issue-based content with dynamic visual packaging generates higher engagement than routine content. The novelty of this research lies in the integration of the POAC management model with a data-driven community management approach in the context of legislative political communication on social media. This research's academic contribution demonstrates that digital content management is not merely technical but also strategic in building political legitimacy and public engagement in the digital space.